English Teachers’ Perception on Teaching Module Guidance in Merdeka Curriculum at SMK Nurut Taqwa Songgon - Ika Winarsih; Wanda Finolia; Fitria Wulan Nanda; Mothar Rafi; Sutami Dwi Lestari (MAN Insan Cendekia Jambi, 2025)
This study evaluates English teachers' perceptions of the teaching module within the Merdeka Curriculum at SMK Nurut Taqwa Songgon. The aim of this research is to assess the quality, relevance, and effectiveness of the teaching module in supporting instructional practices and student learning outcomes. The methodology employed included distributing questionnaires and conducting interviews with six English teachers to gather data on the core components of the module and the appendix. The findings reveal that teachers hold a positive perception of the core components of the teaching module, with favorable assessments regarding the structure, relevance, and understanding of the material. However, there is variation in views on the appendix, with some teachers feeling that the additional information provided is less useful or relevant. These findings support Rogers' innovation adoption theory, which emphasizes the importance of positive perceptions for the effectiveness of new curricula. The study concludes that the teaching module within the Merdeka Curriculum is generally well-received by teachers, but further evaluation and development are needed to enhance the relevance and usefulness of the appendix in supporting the learning process.